Presenilin-1 Familial Alzheimer Mutations Impair γ-Secretase Cleavage of APP Through Stabilized Enzyme–Substrate Complex Formation - Sujan Devkota; Masato Maesako; Michael S. Wolfe (Biomolecules)
Familial Alzheimer’s disease (FAD) is caused by dominant missense mutations in amyloid precursor protein (APP) and presenilin-1 (PSEN1), the catalytic component of γ-secretase that generates amyloid β-peptides (Aβ) from the APP C-terminal fragment C99. While most FAD mutations increase the ratio of aggregation-prone Aβ42 relative to Aβ40, consistent with the amyloid hypothesis of Alzheimer pathogenesis, some mutations do not increase this ratio. The γ-secretase complex produces amyloid β-peptide (Aβ) through processive cleavage along two pathways: C99 → Aβ49 → Aβ46 → Aβ43 → Aβ40 and C99 → Aβ48 → Aβ45 → Aβ42 → Aβ38. Understanding how FAD mutations affect the multistep γ-secretase cleavage process is critical for elucidating disease pathogenesis. In a recent study, we discovered that FAD mutations lead to stalled γ-secretase/substrate complexes that trigger synaptic loss independently of Aβ production. Here, we further investigate this “stalled complex” hypothesis, focusing on five additional PSEN1 FAD mutations (M84V, C92S, Y115H, T116I, and M139V). A comprehensive biochemical analysis revealed that all five mutations led to substantially reduced initial proteolysis of C99 to Aβ49 or Aβ48 as well as deficiencies in one or more subsequent trimming steps. Results from fluorescence lifetime imaging microscopy support increased stabilization of enzyme–substrate complexes by all five FAD mutations. These findings provide further support for the stalled complex hypothesis, highlighting that FAD mutations impair γ-secretase function by promoting the accumulation of stalled enzyme–substrate complexes.